DOES TEACHER'S LIKABILITY INFLUENCE STUDENT'S PERCEPTION OF PHYSICS: AN EMPIRICAL STUDY OF SECONDARY SCHOOL STUDENTS IN EBONYI STATE, NIGERIA (IJOVTECH, 2026)
Physics is one of the most important scientific disciplines taught in Nigeria's secondary school curriculum. Student’s poor performance in physics has become a growing concern. This study aimed to see if teacher likability could impact students' views about physics. A cross-sectional survey was used in this investigation. The survey's participants are secondary school students from Ebonyi State, Nigeria. Male and female senior secondary school students took part in the study. The majority of them came from science class. A total of 139 students were involved in the research. Data was collected using a Teacher's Likability Scale and the Physics Attitude Scale (PAS). The results revealed that most respondents had a negative attitude toward the subject (M = 0.87, SD = 0.35), while only a handful (M = 0.18, SD = 0.39) had a favorable attitude. A linear regression model was used to test the central hypothesis. The findings revealed that teachers' likability statistically significantly influenced students' attitudes toward physics F (1,137), 40.16 p.05. According to the findings, a teacher's likability predicts students' attitudes toward physics. As a result, it is suggested that teachers act more as facilitators than harsh educators.